Slovak Scholars in Bohemia and Moravia and Czech Scholars in Slovakia Before and After the Battle of Biela Hora (1620) - Angela Škovierová (Svetovi, 2024)
During several years of research, we registered a relatively large number of mostly Protestant scholars originating from the territory of today’s Slovakia or those who are considered significant in the context of Slovak cultural history, who in the period before the Battle of Biela Hora (1620) lived and worked in one of the Czech or Moravian cities. This was a very diverse group of humanists including clergymen, professors from Charles University, teachers, scribes, authors of extensive works in Latin or in the vernacular, patrons, or owners of interesting book collections. The article introduces this group of scholars in general, and examines more closely their confessional orientation, as well as what influenced it or subsequently prompted it to change. On the other hand, we also want to briefly note several Czech scholars who, as a result of the changed religious situation in Bohemia, came to Slovakia after the Battle of Biela Hora.